The Effect of Fireweed (Crassocephalum crepidioides) Leaf as an Additional Diet on the Growth of Climbing Perch (Anabas testudineus) - Darsiani Darsiani; Zeist Jordi; Dian Lestari; Dewi Yuniati; Shobrina Silmi Qori Tartila; Suri Purnama Febri (Airlangga University, 2026)
This study aimed to determine the effect of fireweed leaves (Crassocephalum crepidioides) as a dietary supplement on the growth of climbing perch (Anabas testudineus). The study employed a completely randomised design with five treatments, each replicated three times. The treatments administered were as follows: A (5% commercial feed_CF), B (4% CF + 1% fireweed leaves_FL), C (3% CF + 2% FL), D (2% CF + 3% FL), and E (5% FL). For 40 days, climbing perch (31.71 g ± 3.61) were reared in aquariums (water volume 10 L) at a density of 1 fish/L. The parameters observed included weight gain, length gain, specific growth rate (SGR), and daily feed intake. The results showed that the addition of fireweed leaves significantly improved the growth of climbing perch. The best treatment was obtained with a combination of 3% commercial feed (CF) and 2% fireweed leaves (FL). Therefore, this study concluded that fireweed leaves can be used as a feed supplement to support the growth and survival rate of climbing perch.